A diversified vertebrate ichnite fauna from the Feitianshan Formation (Lower Cretaceous) of southwestern Sichuan, China. (January 2016) - Xing, Lida; Lockley, Martin G.; Yang, Geng; Cao, Jun; McCrea, Richard T.; Klein, Hendrik; Zhang, Jianping; Scott Persons, W.; Dai, Hui
Abstract: The Bajiu tracksite exposed on a fine sandstone surface at the top of the Feitianshan Formation, close the contact with the overlying Xiaoba Formation, reveals a saurischian dominated ichnofauna consisting of four sauropod and at least eight theropod trackways. The sauropod trackways display a medium-wide gauge pattern characteristic of titanosauriforms, while the theropod trackways can be subdivided into two distinct morphotypes. One is similar to the ichnogenera Eubrontes and Megalosauripus, the other (cf. Dromaeopodus ) appears to represent a functionally didactyl dromaeosaur where pedal digit II is represented only by an oval basal pad. A single swim track is possibly attributable to a turtle or crocodylian. Such sauropod-theropod dominated ichnofaunas are consistently typical of the red-bed tracksites in the region and useful for characterizing a fauna that is otherwise poorly known from body fossils. The stratigraphic position and late occurrence of the (typical Jurassic) Eubrontes-Megalosauripus morphotype is well known from other Cretaceous localities in China and seems to reflect a peculiarity in the theropod faunas of East Asia.